The Effect Of The Minimum Capital Availability Obligation (CAR) on Profitability (ROA) at Perumda BPR Majalengka, Majalengka Regency - Tia Aprilia Susnita (Return : Study of Management, Economic and Bussines, 2022)
Background: Effect of Minimum Capital Adequacy Requirement (CAR) on Profitability (ROA) at Perumda BPR Majalengka Majalengka Regency. Aim: Capital Adequacy Ratio (CAR) is needed to calculate the capital adequacy of a bank and determine the credit that can be disbursed. Interest profit generated from loans disbursed can increase bank profitability. This study aims to determine the development of the Capital Adequacy Ratio (CAR), to determine the development of the level of profitability (ROA), and to determine the effect of the Capital Adequacy Ratio (CAR) on the level of profitability (ROA) at Perumda BPR Majalengka, Majalengka Regency. Method: The method used in this research is a descriptive method with a quantitative approach. To determine the effect of the Capital Adequacy Ratio (CAR) on the level of profitability (ROA), statistical testing is used. Statistical testing used is the use of linear regression, Pearson correlation coefficient, coefficient of determination, hypothesis testing, and also using the SPSS 24.0 application for windows to strengthen manual calculations. Findings: The results of data analysis using SPSS 24 for windows show that the Capital Adequacy Ratio (CAR) has a significant influence on the level of profitability (ROA) because the t count is greater than the t table or 3.008 > 2.35336 correlation value between Capital Adequacy Ratio (CAR) and profitability. (ROA) based on the research data obtained is 0.757 This value indicates the strength of the relationship is included in the category of a strong relationship. The regression equation is as follows Y = 0.374 + 0.214X. The effect of the Capital Adequacy Ratio (CAR) on the level of profitability (ROA) is 57.3%, while the remaining 42.7% is influenced by factors other than the Capital Adequacy Ratio (CAR) such as credit realization, third-party funds (TPF) and interest and public trust.